An Updated View of the Water Masses on the Northeast Greenland Shelf and Their Link to the Laptev Sea and Lena River. Issue 4 (19th April 2023) - Willcox, E. W.; Bendtsen, J.; Mortensen, J.; Mohn, C.; Lemes, M.; Pedersen, T.‐J.; Holding, J.; Møller, E. F.; Sejr, M. K.; Seidenkrantz, M.‐S.; Rysgaard, S.
Abstract: The Northeast Greenland shelf is a broad Arctic shelf located between Greenland and Fram Strait. It is the principal gateway for sea ice export and sea ice‐associated freshwater from the Arctic Ocean. Sea ice thickness has decreased by 15% per decade since the early 1990s and meteoric freshwater discharge has increased. The consequence of changing sea‐ice and freshwater conditions in the region on ocean dynamics and the biological system remains unknown. Determining the source(s) of freshwater is important to be able to understand how the area will react to future upstream change. Here we present a synoptic survey of the Northeast Greenland shelf and slope with observations of hydrography, the nutrients nitrate, phosphate and silicate, and conservative tracers δ 18 O, δ 2 H, and total alkalinity during late summer 2017. We compare these to previously published values, including those which identify Pacific and Atlantic water, the Siberian shelf seas, and the six largest Arctic rivers. We show that a major source of freshwater on the Northeast Greenland shelf during late summer 2017 is the Laptev Sea and find no conclusive evidence of Pacific Water. Our observations indicate a direct link between Northeast Greenland hydrology and processes occurring on Eurasian shelves. Plain Language Summary: The Northeast Greenland shelf is a shallow marine environment between Greenland and the adjacent Fram Strait, where a large fraction of the Arctic Ocean freshwater is exported into the North Atlantic. To predict the regional response to climate change, it is important to determine what the remote sources of freshwater on the shelf are and how these influence mixing. We compare the chemistry of the water found at different locations on the shelf with those found in other areas of the Arctic Ocean to determine where it comes from and conclude that most of the water on the Northeast Greenland shelf in late summer of 2017 is from the Laptev Sea, while surface waters have subsequently been modified by sea ice melt. Key Points: Northeast Greenland Winter Water is fresher than in the 1990s The cold halocline layer is a brine‐enhanced mixture of river discharge and Atlantic Water The river discharge is primarily sourced from the Laptev Sea